A função social do ecoturismo - Layrargues, Philippe Pomier (Boletim Técnico do Senac, 2004)
Eco-tourism represents a new segment of the tourist market that is drawing a great deal of attention on account of the relations it has fashioned with cultural and ecological dynamics. Nevertheless, its socio-economic context has remained relegated to second place in reflections on how to assess its limitations and potential. Based on the presumed need to draw up public policies of a distributive nature to face Brazil’s concentration of income, this work sets out to analyze the social function of eco-tourism from the view-point of productive and commercial relations in order to see more clearly the role of eco-tourism in social change.